Processos comunicacionais e educacionais em espaços museológicos e instituições culturais: experiências de criação colaborativa na Bienal da Criança e no Museu de Arte Moderna de São Paulo - Barmak, Carlos (2023)
In the context of cultural and museum institutional spaces, studies on creation processes in communication can contribute to reflection on relational, ethical and logical experiences in everyday dialogue with different audiences. In this master's thesis we will present two cultural and educational projects that were intended to introduce into the institutions where they took place, an environment of expressive freedom, intertwining of languages and construction of knowledge. The research has as its theoretical foundation the precepts of transdisciplinarity and the theories and methods of the line of research: creation processes in communication and culture. As results obtained, this master's thesis proposed to present a synthesis of the experience lived at the Fundação Bienal de São Paulo in the context of creating the Bienal da Criança project, and the development of the program, projects and actions in the educational area of the Art Museum Moderna de São Paulo - Educativo MAM - so that it can benefit and contribute to future people interested in this field of work; highlighting their general characteristics, their assumptions and the principles that constituted the bases of these two educational projects